RANCANG BANGUN ALAT PENCETAK KUE BAWANG (Design Construction of Onion Chips Molder) - Robert Tio Hutagalung; Achwil Putra Munir; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2017)
ABSTRACT Manual molding onion chips was considered not effective because the molding process have many steps. The purpose of this research was to design, build, test and analyze the economic value of onion chips molder. This research was conducted in October until December 2015 in the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra, Medan, by literature study, equipment tests and parameters observation. The parameters observed were effective capacity, yield and economic analysis. Based on this research, it was summarized that the effective capacity of the equipment was 30,63 kg/hour and the yield was 97,83%. Economic analysis was as follows: basic costs for the first to the fifth year was Rp.340,09/kg, Rp.340,39/kg, Rp.340,59/kg, Rp.340,80/kg, Rp.341,02/kg respectively. Break even point (BEP) was at 85,36 kg/year of onion chips molded. Net present value (NPV)7,5% was Rp.202.802.837. Internal rate of return (IRR) was 48,5%. Keywords: onion chips, molder, manual ABSTRAK   Pencetakan kue bawang secara manual dinilai kurang efektif karena proses pencetakannya memerlukan banyak tahapan. Penelitian ini bertujuan untuk merancang, membuat, menguji serta menganalisis nilai ekonomis alat pencetak kue bawang. Penelitian ini dilakukan pada bulan Oktober hingga Desember 2015 di Laboratorium Keteknikan Pertanian, Fakultas Pertanian Universitas Sumatera Utara, Medan, dengan cara studi literatur, pengujian alat dan pengamatan parameter. Parameter yang diamati yaitu kapasitas efektif alat, rendemen dan analisis ekonomi. Dari hasil penelitian diperoleh kapasitas efektif alat sebesar 30,63 kg/jam dan rendemen sebesar 97,83%. Analisis ekonomi, biaya pokok untuk tahun pertama sampai tahun kelima berturut-turut yaitu Rp.340,09/kg, Rp.340,39/kg, Rp.340,59/kg, Rp.340,80/kg, Rp.341,02/kg. Alat ini akan mencapai nilai break even point (BEP) apabila telah mencetak adonan kue bawang sebanyak 85,36 kg/tahun. Net present value (NPV) 7,5% sebesar Rp.202.802.837. Internal rate of return (IRR) adalah sebesar 48,5%.   Kata kunci: kue bawang, alat pencetak, manual